Design and Implementation of Multiband Microstrip Patch Antenna for Wireless Applications - Prasad, L.; Ramesh, B.; Kumar, K. S. R.; Vinay, K. P. (Advanced Electromagnetics, 2018)
Multiband phased array antennas are required for today’s multi-function communication applications. Generally Microstrip antenna arrays like Kotch array, Sierpinski array are used, but in some circuits where space is limited, arrays are not used. Therefore, to achieve the multiband operation with limited space, an antenna is designed with E-shaped in combination with split ring resonator to achieve the multiband operation. The simulation and experimental results show that the proposed antenna operates at four different frequencies, 1.8GHz, 3.6GHz, 4.53GHz and 5.73GHz, which can be used for different wireless applications like GSM 1800 (1.71– 1.78 GHz), WiMAX (3.4-3.69GHz) -IEEE 802.16 standards, Wi-Fi/WLAN (5.15-5.82 GHz). All the simulation results like resonant frequency, return loss, radiation patterns and fabricated antenna measured result is presented in this paper. The antenna is simulated using CST 2014 software.